THE CONCEPT OF RECORDING DEEDS IN THE QUR’AN: A CONCEPTUAL DIALOGUE WITH INFORMATION TECHNOLOGY PARADIGMS IN THE ERA OF DIGITAL CULTURE - Ulin Nuha; Ahmad Aminuddin; Izziya Putri Ananda (Universitas Kiai Abdullah Faqih Gresik, 2026)
Digital culture has transformed paradigms of information recording, storage, management, and verification through technologies such as real-time data processing, database management systems, cloud computing, and blockchain. This study reconstructs the concept of recording human deeds in the Qur’an. This study examines the Qur’anic construction of the recording, storage, and accountability of human deeds through the concepts of Kir?man K?tib?n, Kit?b al-A?m?l, and al-Law? al-Ma?f??, and explores their conceptual relevance to contemporary information technology paradigms.Using qualitative library research and the thematic (maudhu’i) tafsir method, the study analyzes relevant Qur’anic verses through content analysis, drawing on classical and contemporary exegetical literature as well as studies in information technology. The results show that the Qur’anic system of recording deeds is structured around three interconnected principles: recording accuracy through the Kir?man K?tib?n, transparency and accountability in information storage through the Kit?b al-A?m?l, and information integrity and immutability through the al-Law? al-Ma?f??. These principles demonstrate functional correspondences with real-time recording, database management systems, cloud computing, and blockchain. However, these correspondences exist solely at the level of conceptual analogy and do not imply ontological parity between revelation and modern technology.